A survey of radiation level in part A of Singapore - Tan, Chow Tat. (2013)
This report summarises the findings author has acquired on surveyed radiation level in Singapore. 492 measurements were recorded from across the whole island, covering rural areas such as industrial estates located at the western, eastern and northern parts of Singapore, to urbanized areas such as housing estates, offices and shopping centres located at the central and southern regions. The report provides a brief overview of radiation, introduces the objectives and the scope of the project. This is followed by a more in-depth discussion on radiation, types of radiation, components which constitute background radiation, health effects associates with radiation, units and instruments used to detect and measure radiation level, including hardware and software used in the present project. The Geiger Meter PM1405 and smartphone GPS were selected, together with the use of MATHLAB software. The standardization of measuring procedure is then described. Results collected shows that building materials might affect background radiation in Singapore. The average radiation level in Singapore is found to be 0.14µSv/h (0.137±0.013µSv/h).